Avances en el diagnóstico y tratamiento de la neumonía adquirida comunitaria en población pediátrica. - Huebla Paca, Alex Miguel (2024)
The main objective of the present project, entitled “Advances in the diagnosis and treatment of Community Acquired Pneumonia in the Pediatric Population”, is to determine the advances in diagnosing and treating community acquired pneumonia among the pediatric population. Being community-acquired pneumonia (NAC) is one of the main pediatric conditions due to the development of the immune system being Streptococcus pneumonia the most prevalent bacterial microorganism causing severe pneumonia; epidemiological surveillance in 2022 at the national level 106-906 cases of lung disease were, as of the year 2023 40.067 cases have been, being Pichincha the provincial with the most cases 15.209; where the most affected age group is 1 to 4 years, with male predominance. The manifestations are characterized by coughing, tachypnea, stretching and unquantified increase in temperature, and most women report frostbite and hyperhidrosis. The diagnosis is based on clinical criteria, history, and physical examination. Treatment is based on determining the magnitude of symptoms, age, and causing microorganisms. Maintenance measures such as hydration, nutrition, antipyretics, and oxygenation are used. The chest ultrasound, in addition to the chest X-ray, is an essential tool for the diagnosis of NAC, allowing to visualize the extent and severity of pulmonary infiltrations. Ultrasound may help standardize clinical practice around primary care and evaluate pneumonia and pleural stroke in infants and children. The use of pediatric ultrasound also has benefits, such as lower costs and the use of trained personnel. Advanced microbiology also plays a crucial role in the precise identification of the causative agent of NAC, especially in cases with atypical clinical presentations or inadequate response to initial treatment. Biomarker and supplementary laboratory tests, such as C-reactive protein (PCR), procalcitonin, IL-6 and leukocyte count, may provide additional information on the severity of NAC and treatment response. The descriptive, documentary and qualitative study, which were analyzed in systematic reviews, studies, metaanalysis, scientific articles and clinical trials related to the diagnosis and treatment of pneumonia acquired in the pediatric community over the last 5 years. It is crucial to implement NAC prevention and control strategies aimed at addressing the specific needs of vulnerable communities, including health promotion, improved access to basic services and implementation of vaccination programs. These strategies are essential for managing the disease and reducing its impact on the pediatric population.